The Implementation of the Paikem Approach by Using the Graphic Media to Increase Students’ Activeness and Learning Outcomes in the Language Subject - Made Aryawan Adijaya (Journal of Education Reseach and Evaluation, 2023)
Student engagement is not optimal and has an impact on learning outcomes, so the PAIKEM approach, aided by graphic media, must be used. The study's goal was to examine the increase in activeness and learning outcomes of Indonesian fourth grade students after using the PAIKEM approach with graphic media. This is a two-cycle classroom action research project. In this study, data was collected through observation and testing methods. The study's findings were analyzed using both descriptive statistical and quantitative descriptive methods. According to the findings of the first cycle of research, the average value of student learning activity was 71 and 71% of classical completeness was obtained. In cycle II, the average value of student learning activity was 86.41, with a classical completeness of 86.41%. The average activeness of 15.41 and 15.41% of classical completeness appears to have increased. The second research cycle yielded an average of 66 student learning outcomes and 66% classical completeness. In cycle II, the average value of student learning outcomes is 85.5, with a classical completeness of 85.5%. There appears to be a 19.5 and 19.5% increase in learning outcomes, respectively. It was concluded that using the PAIKEM approach in conjunction with graphic media could improve the learning outcomes of Indonesian students in elementary school class IV.